Distribution of the CorA Mg2+ transport system in gram-negative bacteria. - Smith, R L (1995)
The CorA Mg2+ transport system is the dominant constitutive uptake mechanism in Salmonella typhimurium and Escherichia coli. Southern blot hybridization and PCR techniques were used to screen a panel of 18 additional gram-negative bacterial species for corA homologs. Virtually all strains tested positive for the presence of corA. Thus, corA appears to be ubiquitous within gram-negative bacteria and is likely their major Mg2+ influx system.